2022
DOI: 10.2147/idr.s343264
|View full text |Cite
|
Sign up to set email alerts
|

Meropenem Target Attainment and Population Pharmacokinetics in Critically Ill Septic Patients with Preserved or Increased Renal Function

Abstract: Purpose Critically ill patients with preserved or increased renal function have been shown to be at risk of underexposure to meropenem. Although many meropenem population pharmacokinetic (PK) models have been published, there is no large prospective population PK study with rich sampling focusing on patients most at risk of suboptimal pharmacokinetic/pharmacodynamic (PK/PD) target attainment. Therefore, the aim of the present study was to evaluate PK/PD target attainment and to perform a thorough … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 37 publications
0
10
0
1
Order By: Relevance
“…Studies with population PK modeling reports variable results and lower meropenem PK/PD TAs for ICU patients than in the present study 5,6,25,26 . Furthermore, in many PK/PD modeling studies with dose simulations and dose recommendations, the clinical endpoints are missing 5–7 .…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…Studies with population PK modeling reports variable results and lower meropenem PK/PD TAs for ICU patients than in the present study 5,6,25,26 . Furthermore, in many PK/PD modeling studies with dose simulations and dose recommendations, the clinical endpoints are missing 5–7 .…”
Section: Discussionmentioning
confidence: 57%
“…24 Studies with population PK modeling reports variable results and lower meropenem PK/PD TAs for ICU patients than in the present study. 5,6,25,26 Furthermore, in many PK/PD modeling studies with dose simulations and dose recommendations, the clinical endpoints are missing. [5][6][7] The high pharmacokinetic variability observed in the present population did not support the progress to dosing simulations from PK modeling.…”
Section: Discussionmentioning
confidence: 99%
“… 8 , 9 The PPK parameters in this study were similar to those previously reported for patients with sepsis. 15 As CG-CCr is estimated using factors such as age, weight, and SCr, it is markedly affected by these factors. Arulkumaran et al 16 reported that SCr values in patients with sepsis were elevated in the first 3 hours, normalized after 12 hours owing to fluid resuscitation, and increased after 24 hours.…”
Section: Discussionmentioning
confidence: 99%
“…Hal ini disebabkan kreatinin klirens pasien ditemukan sebesar 41,17 mL/menit sehingga membutuhkan penyesuaian interval menjadi 12 jam. Meropenem dengan serum kreatinin 26 -50 mL/menit membutuhkan penyesuaian dosis 0,5 -1 g IV setiap 12 jam (Gijsen et al, 2022) Berdasarkan hasil penelitian, dari 21 pasien COVID-19 dengan pneumonia dengan status keluar rumah sakit (KRS) sembuh didapatkan rentang lama pemberian antibiotik seperti pada tabel 6. Antibiotik pada penelitian ini diberikan tidak lebih dari 14 hari.…”
Section: Hasil Dan Diskusiunclassified